2018
DOI: 10.1590/1809-4422asoc0133r2vu18l4td
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Dengue and Socio-Environmental Variables in Capitals of the Brazilian Northeast by Cluster Analysis

Abstract: This article aims to identify the level of similarity between dengue and climatic, sociodemographic and sanitation variables in Brazilian Northeast capitals between 2001 and 2012, by cluster analysis, an explanatory technique used on multivariate data to verify the interrelationship between groups formed by the similar distances among its components. The results, validated by Spearman, showed high correlation (p-value ≤ 0.0001) of dengue with: female subjects between 10-19 years old and over 79 years old; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 16 publications
0
16
0
6
Order By: Relevance
“…Urban households can have different waste streams than rural households, such as ceramics and plastics, which collect water and serve as mosquito larval habitats (Banerjee et al 2015). In Brazil, a study found that some cities with the highest relative levels of sanitation service, municipal trash service and water supply, were among those with the highest dengue fever incidence (DaSilva and Machado 2018). The relationship of municipal trash service with dengue further supports that urban populations are more susceptible to dengue.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Urban households can have different waste streams than rural households, such as ceramics and plastics, which collect water and serve as mosquito larval habitats (Banerjee et al 2015). In Brazil, a study found that some cities with the highest relative levels of sanitation service, municipal trash service and water supply, were among those with the highest dengue fever incidence (DaSilva and Machado 2018). The relationship of municipal trash service with dengue further supports that urban populations are more susceptible to dengue.…”
Section: Discussionmentioning
confidence: 98%
“…These water sources provide potential above and below ground sites for mosquito breeding. The presence of septic systems has been noted to relate to mosquito breeding, including for Aedes mosquitoes that vector dengue (DaSilva and Machado 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the health variables alone do not explain the heterogeneity of the diseases, as their determinants are multiple in aspects and varied factors; however, they are essential elements to explain the occurrence of arboviruses (Santos et al 2000;Buss and Filho 2007). Therefore, the relationship established between arboviruses in the northeast region, notably ZIKV, and basic sanitation is evident (Sommerfeld and Kroeger 2012;Silva and Machado 2018). For instance, in Teresina (Northeastern Brazil), the main area of microcephaly, has serious problems of sanitation, infrastructure, waste management, and vector control (Almeida et al 2019).…”
Section: Anthropogenic Factorsmentioning
confidence: 99%
“…To combat vector-borne diseases, an integrated approach was recommended by Silva and Machado (2018), consisting of (a) environmental management that eliminates mosquito breeding sites and reducing standing water sites; (b) chemical control where repellents and insecticides may be used; (c) biological control against eggs, larvae, and mosquitoes such as using the seed of Moringa oleifera that limit the reproduction of Ae. aegypti (Silva and Machado 2018); and (d) release of altered mosquitoes such as Wolbachia-infected male mosquitoes, sterile mosquitoes, and insects carrying a dominant lethal gene (Silva and Machado 2018). Wang et al (2017) suggested releasing of Wolbachia-harboring female, and male mosquitoes will result in the replacement of Ae.…”
Section: Short-and Mid-term Solutionsmentioning
confidence: 99%
“…Cluster analysis has also been used in epidemic studies such as in dengue study [14][15][16][17][18][19][20]. A study done by Vandhana and Anuradha [17] employed hierarchical clustering analysis in order to classify the dengue in various states of India.…”
Section: Introductionmentioning
confidence: 99%